Biomechanical analysis of the masticatory movement before and after adjusting dental occlusion in equine - Neto, A.O. Paiva [UNESP]; Leite, C. T. [UNESP]; Duarte, C. A.; Dias, D. P.M. [UNESP]; Döwich, G.; Neto, A. Queiroz [UNESP]; Neto, J.C. Lacerda [UNESP] (FapUNIFESP (SciELO), 2018)
The aim of this study was to evaluate through three-dimensional kinematic analysis the influence of occlusal adjustment by tooth wear in masticatory biomechanics of horses. Seven clinically healthy thoroughbred Arabian horses with strong occlusal irregularities were used, of which seven castrated males and one female of between seven and nineteen years of age. Three digital video cameras and seven spherical reflective markers placed on the horses' face were employed. The animals were filmed twice in succession: while chewing hay before and after the occlusal adjustment by tooth wear. Following that, kinematic analysis was made of the movements obtained by means of the images which were synchronized, segmented and reconstructed three-dimensionally with the help of Dvideow program. Mathematical functions were applied in Matlab environment for obtaining the values of the amplitudes of movements. The results of the biomechanical analysis showed that the occlusal adjustment increases the range of mandibular movements in horses.
Keywords: Chewing; Dentistry; Kinematics; Occlusion; Teeth